The Effect of Land Reform on Poverty: A Study of Provinces in Indonesia - Ketut Wahyu Dhyatmika; Munawar Ismail; Putu Mahardika Adi Saputra (AIBPM Publisher, 2022)
Land is an important part especially for the poor because land is able to provide opportunities for the poor to get out of poverty. Land redistribution is one of the policies aimed at reducing poverty levels. This study uses a literature study and descriptive statistic to see the effect of Land reform in the form of land redistribution on poverty. Based on the results of reviews of previous studies, it was found that most concluded that land redistribution had a negative effect on poverty levels. Studies conducted in Indonesia related to land redistribution confirm the results that land redistribution can reduce poverty levels through increasing income from production in the agricultural sector and access to credit. This implies that land redistribution is the right policy to reduce poverty so that it needs to be increased both in terms of number and accuracy of target recipients. Keywords: Poverty. Land Redistribution, Land Reform, literature study, Indonesia